Review of international law and analysis of international commercial contracts - seyd mohamad farnam; mahdi safarifard; elham hosienpour (مهندسی و مدیریت ساخت)
This article is about explaining the nature of the legal system that governs the government's international trade contracts. The government, which until yesterday was a person of international law in the position of exercising political sovereignty, today appears to enter the field of business in order to manage its underground resources in particular. Until yesterday, the host government claimed that this type of contract is subject to the rules of administrative law and therefore the concluded contract is subject to the "national law of the host government"; Today, the apparently new role of the government has been changed by the jurists of the capital world to deny the possibility of applying the legal rules of the host country as rules of administrative law. system has been Assistant Professor of the Faculty of Law and Political Sciences, University of Tehran, the following articles have been published by this author in the Journal of the Faculty of Law and Political Sciences: "The law governing the limits of the powers of managers in joint-stock companies". Jurists have come to the position of recognizing and applying an independent legal system as the "Third Order" or "Transnational Commercial Law Rules" so that the foreign commercial contract concluded by the government is always and without doubt subject to an independent legal system whose fabric is internal and based on National interests are in the hands of international judges under the pretext of international trade interests.